Descriptive Analysis of Verbal Interaction between Teacher and Students in the Classroom by Using FLINT System at the Eighth Grade of UPTD SMP Negeri 3 Gunungsitoli Utara in 2022/2023 - Swit Dwi Fia Zega; Yasminar Amaerita Telaumbanua; Afore Tahir Harefa; Elwin Piarawan Zebua (STABN RADEN WIJAYA WONOGIRI, 2023)
Effective interaction affects the achievement of learning quality, where students are expected to be more active in the classroom than teacher. However, in the learning process that occurred at UPTD SMP Negeri 3 Gunungsitoli Utara, the teacher was more active than the students. Therefore, the research objectives were to describe the types of verbal interactions between the teacher and the students, to find out the most dominant indicator of verbal interactions and the factors of students responding in their own way, and to analyze verbal interactions between the teacher and the students that occurred in the classroom at the eighth grade of UPTD SMP Negeri 3 Gunungsitoli Utara in 2022/2023. The researchers used the descriptive qualitative. Data were obtained from video recordings, field notes, and interviews, and then analyzed using FLINT System. The research results showed that the type of interaction carried out was teacher-learner interaction and the most dominant indicator were Giving Direction and Asking Questions. During the learning process, teacher talk was more dominant, the students interacted when the stimulus was given by the teacher and there were several times when the students were silent. The influencing factors were limited L2 experience, lack of knowledge, students' personality, teaching style and technique, environmental support, topic selection, and class time and size.